Meningkatkan Daya Tarik Ekowisata Desa Siakin melalui Media Promosi Visual Pertanian Bawang Putih Organik - Maharyani, Ni Luh Putu Eka; Kartika, I Gusti Agung Ayu (Sevanam: Jurnal Pengabdian Masyarakat, 2026)
The development of ecotourism in Siakin Village faces challenges in optimizing its natural and cultural potential, particularly organic garlic farming practices,. This community service project aims to enhance the appeal of ecotourism in Siakin Village through the creation and socialization of visual promotional media in the form of flyers. The method employed is qualitative descriptive, with data collection techniques including interviews, observations, and documentation studies, supported by counseling on organic garlic cultivation as high-quality medicinal raw material,,. The results indicate that flyers are effective as both promotional instruments and educational media regarding environmental sustainability values for both the community and tourists,. Despite constraints in design skills and budget limitations, strategic solutions such as design training for the community and the integration of physical and digital distribution were able to overcome these obstacles,,. Through this collaborative approach, visual media has successfully strengthened Siakin Village's image as a sustainable ecotourism destination, which in turn is expected to increase tourist visits and support the long-term economic empowerment of the local community.